2019
DOI: 10.1016/j.omtn.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

miR-31-5p Is a Potential Circulating Biomarker and Therapeutic Target for Oral Cancer

Abstract: MicroRNAs have been proposed as novel biomarkers for the diagnosis and treatment of many types of cancer. The levels of five candidate microRNAs (miRNAs) (miR-99a-5p, miR-31-5p, miR-138-5p, miR-21-5p, and miR-375-3p) in sera from oral cancer patients and paired tumor and normal tissues were detected by real-time qPCR. The diagnostic power of these miRNAs was analyzed by receiver operating characteristic (ROC) curves. Patient-derived xenograft (PDX) models of oral cancer were established and utilized to verify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 52 publications
0
50
0
1
Order By: Relevance
“…19,20 Expression of miR-183-5p has been shown to be associated with the growth and progression of cancer through multiple mechanisms. [21][22][23][24] EMT is a major process to regulate cell migration and invasion. Shikonin reversed the EMT in breast cancer cells via upregulating E-cadherin and downregulating Snail expressions.…”
Section: Shikonin Increased the Level Of Mir-183-5p And Decreased Thementioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Expression of miR-183-5p has been shown to be associated with the growth and progression of cancer through multiple mechanisms. [21][22][23][24] EMT is a major process to regulate cell migration and invasion. Shikonin reversed the EMT in breast cancer cells via upregulating E-cadherin and downregulating Snail expressions.…”
Section: Shikonin Increased the Level Of Mir-183-5p And Decreased Thementioning
confidence: 99%
“…19,20 Expressions of miRNAs, such as miR-183-5p, have been shown to be associated with the growth and progression of cancer through multiple mechanisms. [21][22][23][24] The inhibition of miR-183-5p significantly abolished the effects of tripartite motifcontaining protein 65 (TRIM65), a critical regulator of a variety of cellular processes and tumor progression, on autophagy and cisplatin-induced apoptosis suggesting a critical role of miR-183-5p in mediating the TRIM65regulated autophagy and cisplatin resistance in human lung cancer A549/DDP cells. 21 Another study showed that the expression of long non-coding RNA (lncRNA) taurineupregulated gene 1 (TUG1) was increased in cervical cancer tissues, which was correlated with advanced clinical features and poor overall survival in patient with cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prognosis of patients with TSCC with the same TNM stage is highly variable since it is influenced by a variety of factors (6). Recent reports have suggested that many molecular biomarkers involved in angiogenesis, metastasis, proliferation, and differentiation could be used to improve prognostic precision for TSCC patients (7)(8)(9). However, these expensive laboratory techniques and comprehensive tests are rarely suitable for TSCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…These authors observed that antagomiR-31-5p significantly delayed the tumor growth of oral cancer patient-derived xenografts. In addition, they found significantly reduced p-AKT levels and increased PTEN levels in antagomiR-31-5p treated xenografts, indicating that miR-31-5p could be a therapeutic target in oral cancer via the PTEN/AKT pathway [61].…”
Section: Mirnas As Therapeutic Targetsmentioning
confidence: 98%
“…Importantly, miR-187-5p could act as a potential oncogene promoting proliferation, migration, and anchorage-independent colony formation of oral cancer cells. Recently, Lu et al [61] selected a set of five miRNAs (miR-99a-5p, miR-138-5p, miR-375-3p, miR-21-5p, and miR-31-5p) based on previous miRNA profiling studies and analyzed their expression levels in tissue and serum samples. Although only miR-31-5p was significantly upregulated in tissue and serum samples, the serum expression levels of miR-99a-5p, miR-138-5p and miR-375-3p were significantly related to clinical stage.…”
Section: Plasma and Serummentioning
confidence: 99%